TP005/#272 Contessa/neocon-F trial: neoadjuvant chemotherapy followed by fertility-sparing surgery in FIGO 2018 stage IB2 cervical cancer. (4th December 2022) - Plante, Marie; Trommel, Nienke Van; Schaafsma, Mirte; Oza, Amit; Rodriguez, Angela; Wang, Lisa; Sikorska, Karolina; Ferguson, Sarah; Han, Kathy; Lheureux, Stephanie; Amant, Frederic
Abstract : Objectives: The primary objective of the CONTESSA/NEOCON-F trial (NCT04016389 ) is to assess the feasibility of preserving fertility in women with FIGO 2018 stage IB2 cervical cancer by administering neo-adjuvant chemotherapy (NACT) followed by fertility sparing surgery (FSS). Methods: This ongoing multi-center, phase II clinical trial will accrue 90 premenopausal women, aged between 18 and 40 years, who are diagnosed with lymph-node negative, FIGO 2018 stage IB2 cervical cancer and who have a desire to preserve fertility. Patients will receive three cycles paclitaxel and platinum-based chemotherapy. Following NACT the response will be evaluated by clinical examination and MRI. Patients with complete or partial response (residual lesion <2 cm) will be eligible for FSS: a conization or simple trachelectomy. Patients with suboptimal response (residual lesion ≥2 cm) will go off-study and receive definitive treatment as per local protocol. The follow-up is three years. The primary outcome is the rate of functional uterus defined as successful FSS and no adjuvant therapy. Secondary outcomes include the safety of NACT and FSS, the response rate to NACT, and the recurrence-free and overall survival after two and three years. Furthermore, this trial will evaluate patients' quality of life and ovarian function, and will explore the possibilities for disease monitoring in blood plasma (HPV ctDNA) and cervical scrapes (DNA hypermethylation). Results: 'Trial in progress: there are no available results at the time of submission.' Conclusions: The CONTESSA/NEOCON-F trial is opened for accrual in the Netherlands, Canada, and the United States. Currently, 10% of the target accrual has been reached.